The Concept Of Rejecting The Trinity In Islamic Teaching In Surah An-Nisa Verse 171 (Study Of Tafsir Al-Azhar By Buya Hamka) - Dahliana, Yeti; Satriaji Abimanyu; Rhain, Ainur (Jurnal Sosial Sains dan Komunikasi, 2024)
This article examines the concept of rejecting the Trinity in Islam through the analysis of Surah An-Nisa verse 171, focusing on Tafsir Al-Azhar by Buya Hamka. The method used in this research is categorized as library research. In the verse, Allah rebukes Ahlul Kitab, especially the Christians, who have exaggerated in glorifying the Prophet Isa Alaihis-Salam to consider him as God. Buya Hamka emphasized that Jesus was only a messenger of Allah and not God, so the teaching of Tawhid must be upheld by Muslims. This explanation includes the prohibition not to associate Allah with anything and the importance of respecting prophets without going beyond the limits. This study shows that the rejection of the Trinity is not only theological, but also an attempt to protect the faith of the people from deviation. Thus, Tafsir Al-Azhar provides a comprehensive understanding of the rejection of the Trinity in Islam and emphasizes the importance of maintaining the oneness of God as the core of religious teachings.